Grammatical characteristics of children's conversational utterances that contain disfluency clusters. - Logan KJ; LaSalle LR (Journal of Speech, Language & Hearing Research, 1999)
Selected characteristics of disfluent conversational utterances with and without disfluency clusters were examined in 14 children who stutter (CWS) and 14 children who do not stutter (CWNS). For CWS, utterances with disfluency clusters contained significantly more syllables and clausal constituents than disfluent utterances without clusters, which, in turn, contained significantly more syllables, clauses, and clausal constituents than fluent utterances. For both groups of children, disfluency clusters coincided significantly more often with utterance or clause onset than they did with grammatical constituents located elsewhere within an utterance. CWNS produced a significantly greater percentage of disfluency clusters that contained grammatical revision than did CWS. No significant between-group differences were observed in terms of the number of syllables, clauses, or clausal constituents within cluster-inclusive utterances. Findings are taken to suggest that disfluency clusters are typically produced within the most complex linguistic contexts and that they reflect the effects of producing multiple syntactic constituents within an utterance.